Psychological distress and postponed fertility care during the COVID-19 pandemic - Lawson, Angela K. (J Assist Reprod Genet, 2021)
PURPOSE: To evaluate perceptions of delayed fertility care secondary to the COVID-19 pandemic. METHODS: This was a cross-sectional anonymous survey of N = 787/2,287 patients (response rate = 42.6%) from a single academic fertility center. Participants were randomized 1:1 to receive supplemental educational explaining the rationale behind recommendations to delay fertility treatments due to the COVID-19 pandemic. Assessment of well-being was conducted via the Personal Health Questionnaire Depression Scale, the Generalized Anxiety Disorder-7, the Ways of Coping-Revised, the Appraisal of Life Events Scale, and influence of supplemental education on agreement with ASRM COVID-19 Taskforce recommendations and associated distress. RESULTS: Participants in the education v. no education groups were 35.51 (SD = 4.06) and 37.24 (SD = 5.34) years old, married (90.8% v. 89.8%), had a graduate degree (53.9% v. 55.4%), > 1 year of infertility (73.4% v. 74.4%), and were nulliparous (69.0% v. 72.6%), with moderate to high distress (64.9% v. 64.2%) (ns). Distress was related to age, duration of infertility, and engagement in social support seeking and avoidant coping strategies (P < 0.001). Agreement with recommendations was related to receipt of supplemental education, history of pregnancy loss, and use of cognitive coping (P = 0.001). CONCLUSION: Most participants were distressed by the delay of treatments. Supplemental education increased acceptance of recommendations but did not decrease distress. Future treatment delays should include education related to and assessment of understanding of recommendations, and inclusion of mental health professionals in patient care. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10815-020-02023-x.